LCC18, a benzamide‐linked small molecule, ameliorates IgA nephropathy in mice - Yang, Shin‐Ruen; Hua, Kuo‐Feng; Takahata, Akiko; Wu, Chung‐Yao; Hsieh, Chih‐Yu; Chiu, Hsiao‐Wen; Chen, Cheng‐Hsu; Mukhopadhyay, Debabrata; Suzuki, Yusuke; Ka, Shuk‐Man; Huang, Hsu‐Shan; Chen, Ann (The Journal of pathology, 2021)
IgA nephropathy (IgAN), an immune complex‐mediated process and the most common primary glomerulonephritis, can progress to end‐stage renal disease in up to 40% of patients. Accordingly, a therapeutic strategy targeting a specific molecular pathway is urgently warranted. Aided by structure characterisation and target identification, we predicted that a novel ring‐fused 6‐(2,4‐difluorophenyl)‐3‐(3‐(trifluoromethyl)phenyl)‐2H‐benzo[e][1,3]oxazine‐2,4(3H)‐dione (LCC18) targets the NLRP3 inflammasome, which participates in IgAN pathogenesis. We further developed biomarkers for the disease. We used two complementary IgAN models in C57BL/6 mice, involving TEPC‐15 hybridoma‐derived IgA, and in gddY mice. Moreover, we created specific cell models to validate therapeutic effects of LCC18 on IgAN and to explain its underlying mechanisms. IgAN mice benefited significantly from treatment with LCC18, showing dramatically improved renal function, including greatly reduced proteinuria and renal pathology. Mechanistic studies showed that the mode of action specifically involved: (1) blocking of the MAPKs/COX‐2 axis‐mediated priming of the NLRP3 inflammasome; (2) inhibition of ASC oligomerisation and NLRP3 inflammasome assembly by inhibiting NLRP3 binding to PKR, NEK7 and ASC; and (3) activation of autophagy. LCC18 exerts therapeutic effects on murine IgAN by differentially regulating NLRP3 inflammasome activation and autophagy induction, suggesting this new compound as a promising drug candidate to treat IgAN. © 2020 The Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.